The challenges and actual questions of the agriculture in Yemen - Al-sabai, Abdulghani; Neszmélyi, György Iván (Studia Mundi – Economica, 2019)
Agriculture employs more Yemenis than any other sector and spate irrigation is the largest source of irrigation water. Spate irrigation however is growing increasingly difficult to sustain in many areas due to water scarcity and unclear sharing of water amongst users. Mostly due to high population growth, misguided agricultural development and the growth of qat, a lack of law enforcement to regulate water use, and a vulnerable climate to climate change, the crisis may soon reach catastrophic levels. The agriculture uses 93% of the potable water, and does not actively encourage sustainable water saving techniques. Qat (Catha edulis; recreational drug) cultivation uses 40% of the potable water. The water crisis could be mitigated by reducing qat production.
Keywords: Yemen; sustainable agriculture; agricultural policy; irrigation